PENGARUH PEMBELAJARAN INTEGRATIF DAN PBL TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA SMAN 1 TELUK PAKEDAI - Martina, Dwi; Mirza, Ade; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the learning model that can develop students’ mathematical connections between two models of learning, that are Problem Based Learning (PBL) model and integrative learning model on three-dimensional space topic in Class X of SMAN 1 Teluk Pakedai. The research method used was quasi experimental with The Matching-Only Postest-Only Control Group Design as the research design. The sample of this research consisted of two classes: Class XB and X C. The result of data analysis using U-Mann-Whitney test showed that there was no difference of mathematical connection ability between the students hwo were tough by using Problem Based Learning (PBL) model and those who were treated by using integrative learning model. In result Problem Based Learning (PBL) model and integrative learning model can be used to develop students’ mathematical connection ability. This is proved by  the average mathematical connection ability score of the students in Problem Based Learning (PBL) model and integrative learning model which are 65.67 and 64 respectively.Keyword : mathematical connection ability, problem based learning  model, integrative learning model